Kinetics and Mechanism of Ru(III) Catalysed Oxidation of Sodium Thioglycollate by Alkaline Hexacyanoferrate(III) Ion - Singh, B.N.; Singh, S.N.; Prasad, Arjun (Asian Journal of Chemistry, 2010)
Kinetic data on Ru(III) catalysed oxidation of sodium thioglycollate by alkaline solution of hexacyanoferrate(III) has been reported. The reaction follows zero-order kinetics in hexacyanoferrate(III) while first order dependence on each sodium thioglycollate, OH and Ru(III) was observed. A suitable mechanism consistent with kinetics data has been proposed.